2016
DOI: 10.1038/srep23043
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming by Hexosamine Biosynthetic and Golgi N-Glycan Branching Pathways

Abstract: De novo uridine-diphosphate-N-acetylglucosamine (UDP-GlcNAc) biosynthesis requires glucose, glutamine, acetyl-CoA and uridine, however GlcNAc salvaged from glycoconjugate turnover and dietary sources also makes a significant contribution to the intracellular pool. Herein we ask whether dietary GlcNAc regulates nutrient transport and intermediate metabolism in C57BL/6 mice by increasing UDP-GlcNAc and in turn Golgi N-glycan branching. GlcNAc added to the drinking water showed a dose-dependent increase in growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 63 publications
4
82
0
Order By: Relevance
“…GlcNAc has recently been reported to promote glucose, glutamine, and fatty acid uptake in liver and/or adipose tissue via branching induced increases in surface retention of metabolite transporters (Ryczko et al, 2016). Similarly, we observed that modifying branching in T cells with GlcNAc or kifunensine altered glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…GlcNAc has recently been reported to promote glucose, glutamine, and fatty acid uptake in liver and/or adipose tissue via branching induced increases in surface retention of metabolite transporters (Ryczko et al, 2016). Similarly, we observed that modifying branching in T cells with GlcNAc or kifunensine altered glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the β(1,6)GlcNAc branch on N-glycans is readily detected by enhanced binding of the plant lectin L-PHA to glycoproteins, and cannot occur on hybrid N-glycans. It has most recently been shown that by increasing GlcNAc levels in cells and mice, compensation of N-glycan levels may occur via enhanced metabolism and increased UDP-GlcNAc levels in Mgat5 null mice [74]. In the absence of MGAT5, the glucagon receptor in liver and hepatocytes is functionally impaired, and hexosamine biosynthesis is reduced [75].…”
Section: Pathway-specific Glycans That Affect Postnatal Developmentmentioning
confidence: 99%
“…Altering glycostructures in production processes is mostly done by variation of production conditions or by changing the activity level of specific glycosyltransferases and glycosyl hydrolases and has primarily been studied on glycoproteins with a single N-glycosylation site (monoclonal antibody) (22,(29)(30)(31)(32)(33). The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36).…”
mentioning
confidence: 99%